2011
DOI: 10.4194/trjfas.2011.0211
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Meat yield, biochemical composition, and fatty acid profile of farmed brook trout (Salvelinus fontinalis), Black Sea trout (Salmo trutta labrax) and their hybrids were compared. Hybrids contained significantly higher carcass and meat yield values than brook and Black Sea trout. Although the weight percent head and bone (brook trout as 13.14, 1.66 %, Black Sea trout as 13.52, 1.22 % and their hybrids as 13.92, 1.44 %) of the species were similar, fin, carcass, gonad, liver, internal organs and meat yield of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…Fatty acid profiles varied between sexes, with females containing greater proportions of SFA and MUFA, and males numerically more PUFA, particularly when expressed on a total body (rather than fat tissue) basis. Similar findings have been reported in the cultured brook trout Salvelinus fontinalis , Black Sea trout Salmo tutta labrax (Şahin et al., 2011), tilapia O. niloticus (Abelti, 2017) and the sea lamprey Petromyzon marinus (Happel, Rinchard & Czesny, 2017). These results indicate that both sexes may possess different mechanisms for (or different requirements/pressures on) metabolism of certain fatty acids.…”
Section: Discussionsupporting
confidence: 86%
“…Fatty acid profiles varied between sexes, with females containing greater proportions of SFA and MUFA, and males numerically more PUFA, particularly when expressed on a total body (rather than fat tissue) basis. Similar findings have been reported in the cultured brook trout Salvelinus fontinalis , Black Sea trout Salmo tutta labrax (Şahin et al., 2011), tilapia O. niloticus (Abelti, 2017) and the sea lamprey Petromyzon marinus (Happel, Rinchard & Czesny, 2017). These results indicate that both sexes may possess different mechanisms for (or different requirements/pressures on) metabolism of certain fatty acids.…”
Section: Discussionsupporting
confidence: 86%
“…According to calculations, the meat yield of Black Sea trout's fifth genereation was calculated as 60.30±1.91% in fillet size. Atasaral Sahin et al (2011) found meat yields raitos as 65.39% for Salmo trutta labrax, 67.28% for Salvelinus fontinalis and 69.83% for their hybrid. Also, Akhan et al (2010) stated that meat yield of Rainbow trout that reared in Black Sea is vaired between 66.06±3.03% and 70.96±2.55%.…”
Section: Resultsmentioning
confidence: 99%
“…The abdominal part of the muscle tissues are major fat storage sites in Salmonids (Nanton et al, 2007). Likewise, Black Sea trout is rich in terms of fatty acids (Sahin et al, 2011) and moisture and fat are exist inversely correlated in food according to Dean (1990). Also, muscles need to carbohydrates which are mostly stored in muscles in the form of glycogen (Torgersen et al, 2014) in order to compensate energy requariment for swimming (Palstra and Planas, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The amount of power for the lowest solar irradiation in a year was found. With the increase in the irradiation, the amount of power increases slightly [17]. Another obtained result of the measurements is that the voltage of the solar cells maximum operating point changes between 15-20 V. Therefore, it is impossible for the solar panels to feed a 24 V battery directly.…”
Section: Solar Panel Installation and Measurementsmentioning
confidence: 90%